10+2x=16-4x

Simple and best practice solution for 10+2x=16-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+2x=16-4x equation:


Simplifying
10 + 2x = 16 + -4x

Solving
10 + 2x = 16 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
10 + 2x + 4x = 16 + -4x + 4x

Combine like terms: 2x + 4x = 6x
10 + 6x = 16 + -4x + 4x

Combine like terms: -4x + 4x = 0
10 + 6x = 16 + 0
10 + 6x = 16

Add '-10' to each side of the equation.
10 + -10 + 6x = 16 + -10

Combine like terms: 10 + -10 = 0
0 + 6x = 16 + -10
6x = 16 + -10

Combine like terms: 16 + -10 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| 7x-2/6=1 | | (3x-18)+3x=180 | | -3[h+7]=-18 | | -4(7-1)= | | (a+4)(a+6)=63 | | 3x+13-4=5x+3 | | 25p^2-81= | | (z-7)(z+3)=-24 | | 2x^3+11x^2-67x-36=0 | | (5x+4)-(-8x)= | | 4x+y+2x+y= | | D=4n+na | | 5x-0y=14 | | 5m^2=-35m+40 | | 12y^2+49y+30= | | p/-5=-2/5 | | (2x-2)+(x+1)+x+(x+1)=x+(2x-9)+(x+1)+(x+8)+x | | P=4L+3w | | 10(z-4)=(12)z/2 | | 9pq^4-9pr^4=0 | | 2h^2-11h-40= | | 3x/6x^3 | | -(4x-2y-2)= | | 0=8d^2-26d-15 | | 2(m+4)-3m=14 | | (X+8)=29 | | log[5](2x^6)=0 | | z/5-5=7/6 | | -50=-6x-5(-2x+18) | | x/12-3=11/24 | | 8+3x=2x-9 | | 2x^3+21x^2=40x |

Equations solver categories